The effects of household income shocks on migration and employment - Kosec, Katrina; Song, Jie (International Food Policy Research Institute, 2018)
How do income shocks affect migration and employment decisions, and do they differentially impact women and men? Income fluctuations are ubiquitous in the developing world; they may stem from natural disasters, health shocks, commodity price fluctuations, insecure property rights, unreliable public and private service delivery, or a host of other sources. Poor households are often under-insured against such shocks, with important consequence for their welfare. Less is known about how such shocks differentially affect individual women and men, so taking a gender lens to income shocks is critical.